Heroism as a Social Phenomenon: Features of Symbolic Reflection - Голденштейн, Катерина Олександрівна (Київський національний університет імені Тараса Шевченка, 2024)
The social role of symbolism is studied as one that gives political life and political actions a special meaning. On this basis, the phenomenon of «heroism» in the structure of the symbolic policy of the state is considered. The essence and functions of symbols of heroization, the mechanism and methods of its symbolization and introduction into public consciousness are analyzed. The significance of creating a «hero image» as a way of politically conditioned use of social activity is revealed. The historical origins of the «hero image» and the factors of its influence on sociopolitical processes are shown using examples, including the function of preserving and producing nationally oriented values, as well as speculation in order to ensure the dominance of certain political forces. It is proved that the formation of heroic symbols is one of the key ideological instruments of influence on the psychology of citizens in general and at the same time is a phenomenon of mass, largely mythologized consciousness. The process of forming heroic symbols and types of heroic acts, and the features of their use by political propaganda are analyzed. The specifics of the formation and symbolic representation of the «hero image», its place in the historical memory of modern society are reflected. The possibilities and prospects of interpreting the phenomenon of heroism in modern Ukraine, taking into account the realities of the Russian-Ukrainian war, are revealed.

Досліджено соціальну роль символізму, як такого, що надає політичному життю, політичним діянням особливого сенсу. На цій основі розглянуто феномен «героїзму» в структурі символічної політики держави. Осмислено сутність і функції символів героїзації, механізм і методи її символізації та впровадження в суспільну свідомість. Розкрито значення створення «образу героя» як способу політично зумовленого використання соціальної активності. Показано на прикладах історичні витоки «образу героя» та чинники його впливу на суспільно-політичні процеси, включаючи функцію збереження та продукування національно орієнтованих цінностей, а також спекуляції з метою забезпечення панування певних політичних сил. Доведено, що формування героїчних символів є одним із ключових ідеологічних інструментів впливу на психологію громадян загалом і водночас є феноменом масової, значною мірою міфологізованої свідомості. Проаналізовано процес формування героїчних символів та типи героїчних вчинків, особливості їх використання політичною пропагандою. Відображено специфіку формування та символічного відображення «образу героя», його місце в історичній пам›яті сучасного суспільства. Виявлено можливості і перспективи інтерпретації феномена героїзму в сучасній Україні з урахуванням реалій російсько-української війни.
Героїзм як соціальний феномен: особливості символічного відображення
Keywords: symbolism; symbolic politics; political power; heroism; hero; deheroization; political ideology; mythological consciousness; символізм; символічна політика; політична влада; героїзм; герой; дегероїзація; політична ідеологія; міфологічна свідомість